Cell free expression of hif1α and p21 in maternal peripheral blood as a marker for preeclampsia and fetal growth restriction. - Osnat Ashur-Fabian; Gil M Yerushalmi; Shali Mazaki-Tovi; David M Steinberg; Inbal Goldshtein; Michal Yackobovitch-Gavan; Eyal Schiff; Ninette Amariglio; Gideon Rechavi (PLoS ONE, 2012)
Preeclampsia, a severe unpredictable complication of pregnancy, occurs in 6% of pregnancies, usually in the second or third trimester. The specific etiology of preeclampsia remains unclear, although the pathophysiological hallmark of this condition appears to be an inadequate blood supply to the placenta. As a result of the impaired placental blood flow, intrauterine growth restriction (IUGR) and consequential fetal oxidative stress may occur. Consistent with this view, pregnancies complicated by preeclampsia and IUGR are characterized by up-regulation of key transcriptional regulators of the hypoxic response including, hif1α and as well as p53 and its target genes. Recently, the presence of circulating cell-free fetal RNA has been documented in maternal plasma. We speculated that pregnancies complicated by preeclampsia and IUGR, will be associated with an abnormal expression of p53 and/or hif1α related genes in the maternal plasma. Maternal plasma from 113 singleton pregnancies (72 normal and 41 complicated pregnancies) and 19 twins (9 normal and 10 complicated pregnancies) were collected and cell free RNA was extracted. The expression of 18 genes was measured by one step real-time RT-PCR and was analyzed for prevalence of positive/negative expression levels. Results indicate that, among the genes examined, cell free plasma expressions of p21 and hif1α were more prevalent in pregnancies complicated by hypoxia and/or IUGR (p<0.001). To conclude, we present in this manuscript data to support the association between two possible surrogate markers of hypoxia and common complications of pregnancy. More work is needed in order to implement these findings in clinical practice.